PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARARAN TEMATIK TERPADU MENGGUNAKAN MODEL PEMBELAJARAN PORTOFOLIO DI KELAS V SD - Ulfah Elkhaira; Reinita Reinita (Cerdas Proklamator, 2020)
This study aims to describe the improvement of learning outcomes using the Portfolio model in integrated thematic learning for fifth grade elementary school students. In its implementation, the teacher has not used a learning model that can arouse student enthusiasm, and does not provide problems with learning and student work results are not stored together so it is difficult to see student development. This type of research is Classroom Action Research and uses qualitative and quantitative approaches. The subjects of this study were students of grade V SD. The data of this study were the results of observations and tests of each learning improvement action by applying the Portfolio model. This portfolio model has 6 stages, namely "1) identifying problems, 2) selecting problems for class studies, 3) gathering information about problems studied in class. 4) developing portfolios in class, 5) collection of materials, 6) portfolio presentation section.